Ações educativas de enfermeiros no contexto de unidades de internação hospitalar - Rigon, Angelita Gastaldo (2011)
The education dimension presents itself in nursing work through health education, strengthening the role of nurses as an educator, with a view to promoting health. In the professional experience, in units of hospital, it was noted that health education is developed, but in general, under the aegis of the transmission of knowledge in a traditional way, and not as a strategy to health promotion. This is a qualitative research aimed to know the concepts of health education for nurses working in units of hospital at a teaching hospital; characterize the educational actions of nurses and discuss the educational practice of those nurses with teaching trends in education. The production data was obtained through the Creative Sensitive Method. It developed the Dynamics of Creativity and Sensitivity (DCS) Weaving Stories, Tree of Knowledge and Almanac with 10 nurses from units of hospital at a teaching hospital in 2010, May and June. Data were submitted to discourse analysis in his stream French, and applied the analytical tools: metaphor, polysemy and paraphrase. The results pointed out that nurses develop the practice of health education on a daily basis by orientation, in the day care and the guidelines for hospital discharge. These activities are developed in groups and/or individual counseling at the bedside, based on scientific knowledge. They pointed out as difficulties the different realities brought by patients to the hospital, the lack of adequate physical infrastructure, lack of staff and time. A tension between the pedagogical models critical and not critical is noted, but their practice, still tending to the traditional pedagogical model prescriptive. It is recommended an investment in training and continuing education, seeking integration between care, education and research. Thus, it aims to promotion and qualification of care practices and the enhancement of health education by nurses in the context of hospitalization.